Uses of macro social theory: a social housing case study - Bevan, Chris; Cowan, Dave (Wiley, 2016)
This article reflects on the use of macro social theoretical perspectives to explain micro social issues. It uses social housing allocations as a case study of the issues that arise in such explanations. There has been a number of important social theoretical examinations of social housing allocation schemes in recent years, spanning socio-legal studies. In contrast to those other studies, we argue that “cookie-cutter” theory is insufficient because they can overlook other positions and counter-factual scenarios. We draw on a sample of local authority allocation schemes to reflect on the increasing category of excluded households which we term “unhouseables” (an expression which is commonly used by housing officers) – those households which are excluded from appearing on such schemes because of their former housing deviance or some other disqualification. We offer a set of reflections grounded in our data, which focus on sustainability. Thus, rather than point to particular rationalities or the like, we point to particular housing issues as explanatory factors – including the declining stock and financial “competitiveness” of social housing management – as well as a rise in punitiveness.